Preventing Thalasemia: Parents’ Awareness of Thalassemia - mutia anggraini; Ai Mardhiyah; Aat Sriati (Universitas Padjadjaran, 2018)
In Indonesia, thalassemia is a major disease which increases its number every year. There were 7,238 patients of thalassemia major in Indonesia in 2016. The highest number was from West Java, 3,039 patients. Thalassemia is preventable. The increasing number of Thalasemia patients impacted the bigger cost of supportive treatment such as blood transfusion, iron chelation for a lifetime, and the cost of treatment when complications occur. In addition, patient and family also should deal with the psychology burdens. This study was to identify parents’ awareness of thalassemia towards thalassemia prevention in a public hospital in Bandung. This study applied quantitative descriptive method. It involved 99 parents of thalassemia children. The samples were chosen using the accidental sampling technique. Data were analyzed using descriptive statistic. The data were collected using a modification of Thalassemia Awareness Quesionnaire (TAQ). The results showed that the majority of parents 53 (53.4%) had low awareness of thalassemia, and 47 (46.5%) of parents had high awareness. Similarly, the majority of parents had low awareness of thalassemia prevention 58 (58,5%), and only 42 (41,4%) of parents had a high category of awareness. Developing of strategy or program to improve the awareness of parents with thalassemia towards thalassemia prevention is needed. Nurses have a role as a provider and educator of thalassemia health information and prevention.